Validation of the CIMEP model for the development of research competence in primary school teachers - Hernández-Escorcia, Rubén Darío; Reynés, Miguel; Quesada Pallarès , Carla (Revista Complutense de Educación, 2025)
INTRODUCTION. Investigative competence is a transversal element in the curriculum today and plays an important role in the pedagogical practice of today´s teachers as an element of innovation. Although spaces for reflection have been generated, concerning this competence, they take the university as the epicenter and context of interest, sometimes leaving aside the school context as a place where working teachers can continue to grow on the development of this competence. Therefore, the purpose of this research was to identify the dimensions and categories that make up the CIMEP model to create and validate a tool that evaluates the development of research competence in working teachers; and evaluate the CIMEP model in three Latin American countries, for the development of the competence of interest. METHODOLOGY. The methodology implemented was mixed, with a derivative sequential exploratory design. The qualitative stage consisted of a validation of the model through the rubric, by a panel of 12 experts; the quantitative part included the collection and statistical analysis of the data which operationalize the model that is proposed with a sample of 665 participants from the countries of Colombia, Ecuador, and México of the Salle educational network. RESULT. The statistical validation allowed us to reconsider the model from seven to four dimensions, as well as from 20 to 18 categories, as elements that make up the research competence. DISCUSSION. The proposed model adjusts to the reality of the three countries in terms of structure, although is it necessary to develop and implement strategies with teachers for the development of said competence. It is urgent that teachers have an evaluation tool that allows them to self-evaluate in relation to the elements of research competence.
Keywords: competence; research competence; educational research; teachers; primary education